Investigations to reveal the nature of interactions of Bovine hemoglobin with Curcumin nanoparticle using spectroscopic techniques - S.Bakkialakshmi, S.Chithra (International Journal of Modern Agriculture, 2021)
Curcumin is a major bioactive compound found in the Curcuma longa rhizome. The Curcumin Nanoparticles System (Cur-NS) was developed through the process of ionic gelation and defined by the study of particle size, FTIR and SEM. This research aims to explore the relationship of ultraviolet-visible (UV-Vis) absorption, fluorescence, time-resolved fluorescence, synchronous fluorescence and molecular docking methods between the Curcumin nanoparticle system (Cur-NS) and Bovine hemoglobin (BHb). The findings showed that, through the increase in Cur-NS concentration, the fluorescence intensity of BHb was reduced. There was an estimate of binding constants and the number of binding sites. The binding distance to the tryptophan residues of BHb between Cur-NS was 2.23 nm. Results of UV-Vis spectra, synchronous fluorescence spectra, have shown that Cur-NS can alter the confirmation of BHb, which may influence the physiological functions of hemoglobin. In addition, the findings of molecular docking revealed that the experimental fluorescence results were in accordance with the results obtained by molecular docking.